Pemanfaatan Mesin Pencacah Rumput pada Kelompok Ternak 99 Farm - Worldailmi, Elanjati; Dwi Annisa, Putri; Setyawan , Ahmad Mahfudh; Rahman , Dju Farhain; Yaqin , Ichsan Ainul; Ichwan , Muhammad (Journal of Appropriate Technology for Community Services, 2024)
The 99 Farm Livestock Group was founded with the aim of improving the welfare of local communities through goat farming activities. From initially having only 9 goats, this group has grown to a total of 50 goats. This group faces several main challenges in the animal feed processing process, which is carried out conventionally by searching for wet grass every day and feeding it twice a day using the manual chopping method. Meanwhile, the manual enumeration process becomes inefficient and takes time and energy. In addition, the availability of grass is becoming increasingly limited due to reduced land and changes in weather. The solution that is considered appropriate is grass fermentation processing, but this also requires chopping first. To overcome this problem, this community service activity aims to increase the amount of optimal animal feed available and increase knowledge, utilize appropriate technology in the form of grass chopping machines, as well as the skills of breeders in using this technology. The urgency of this activity is to provide solutions for farmers to provide sustainable and effective feed. This service activity was carried out starting from surveys and observations, designing grass choppers, making machines, and socializing their use for breeders. This machine was designed taking into account the specific needs of farmers and local conditions, including the use of an electric motor for efficiency and the provision of a UPS system to overcome the problem of power outages that often occur in rural areas.